(3TQM QSGdI EKHGJ GdhGLHs - (3LdGd GdOjf eMeO Hf CSYO GdUOjbj GdOhGfj, GdOhGfj,J (B918 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje agPg ahGFO TQjaI hfcGJ dWjaI hGajI ai Md QSGdI EKHGJ GdhGLH GdeTJedI Ydi GdObGFb ai JMbjb CYdi GdeWGdH ddehdi GdeMbb eMeO GdOhGfi hgGCfG CTQY ai GdebGUO HYhf Gdedc GdeYHhO s
(3BNQgG (B:s
(3hEf CQOJ ajg JaUjd GdcdGe aCQLY Edi eG PcQg GdeUfa ai MGTjI TQM GdJLQjO hdg eRjO JhVjM GdMGd ai GdhLhO GdPgfi djS cPdc JeJ GdQSGdI HYhf Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B32s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B842s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdadSaI hGdefWbs